Estudo comparativo da evapotranspiração de referência entre localidades no estado de são paulo e na província de Habana - Sousa Pereira, Francisca Franciana [UNESP]; Dal Pai, Enzo [UNESP]; Vázquez Montenegro, Ranses J.; Sánchez Román, Rodrigo Máximo [UNESP]; Orellana González, Alba María Guadalupe [UNESP]; Escobedo, João Francisco [UNESP] (My University, 2016)
FAO proposed the reference evapotranspiration to compare evapotranspiration in different areas, because most equations employed in estimating evapotranspiration are empirical and limited to be used in local and climates similar to those in which they were determined. The objective of this study was to analyze the difference in calculated values of ETo for Botucatu and Piracicaba (Brazil) and Güira Melena (Cuba), based on 30-year data. Seasonal differences between years and locations were assessed and subsequently the influence of local climates on these ETo values differences. Climatic elements maximum (Tmax) and minimum temperature (Tmin), relative humidity (RH), wind speed at 2 m height (U2) and solar radiation (n) were obtained from conventional meteorological stations. Evapotranspiration values in Cuba were higher during summer months in the Northern Hemisphere. The highest evapotranspiration values in Botucatu and Piracicaba occurred in summer months in the Southern Hemisphere. Correlation exists between the three locations with the same distance between them. It was concluded from the methodology used that the three localities have different evapotranspiration values and despite being in different hemispheres the evapotranspiration among Piracicaba and Güira Melena are closer than the one verified between Botucatu and Piracicaba.
Comparative study of reference evapotranspiration between localities in São Paulo state and in the Habana Province
Keywords: Evapotranspiration; Irrigation; Penman Monteith; Water requirement; Water resources